Confined Synthesis of Axial Chlorine Coordinated Single-Atom Nanozyme Within Liposomes for Sensitive Immunoassay - Chu, Chenchen; Jiang, Mingyang; Zhang, Yubei; Feng, Kun; Hua, Chaolei; Wu, Lie; Chen, Yijie; Ji, Ling; Gao, Xitong; Yu, Xue‑Feng; Geng, Shengyong; Zhou, Wenhua (Nano-Micro Letters, 2026)
Single-atom nanozymes (SANs) are considered as the most promising candidates for signal amplification in biosensing applications. However, maintaining the integrity of active sites during functionalization while preserving catalytic performance in biological environments remains a critical challenge. Here, we present a low-temperature-photochemical synthesis strategy for constructing platinum single-atoms within liposomes (PtSANs@Lipo), achieving atomic-level regulation of SANs active sites through axial chlorine (Cl) coordination engineering. The PtN3Cl2 coordination structure, validated by synchrotron X-ray absorption spectroscopy, induces optimal d-band center modulation giving a remarkably low determining step energy barrier compared to conventional PtN3 configurations. This architecture further enables non-contact functionalization via liposomal encapsulation, fully preserving catalytic activity while preventing catalytic sites occupation by antibody, thereby reducing the Michaelis constant (Km) value by 50-fold compared to direct modification onto Pt single-atoms. The constructed immunosensor based on PtSANs@Lipo demonstrates highly sensitive detection of viral pathogens, including influenza A virus H1N1, SARS-CoV-2, and influenza B virus antigens with limits of detection as low as 0.42, 2.23, and 0.36 fg mL−1, respectively. This work establishes a paradigm for bio-adaptive nanozyme design through synergistic coordination engineering and liposomal functionalization architectures, and may thus provide a universal approach for signal amplification in point-of-care diagnostics. Highlights: 1 Axial chlorine coordination engineering constructs PtN3Cl2 single-atom nanozymes inside liposomes via a low-temperature photochemical method. 2 The unique structure lowers the reaction energy barrier and enables antibody conjugation without blocking active sites, reducing Km by 50-fold. 3 The resulting immunosensor achieves ultra-sensitive detection of viral antigens with detection limits as low as 0.36 fg mL-1.